Social ComparisonDan BodyDissatisfaction Dengan Kesejahteraan Psikologis PadaRemaja - Lubis, Raisya Shaffa Diela; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This study is a quantitative research aimed at examining the relationship between social comparisonand bodydissatisfactionwith psychologicalwell-beingamongInstagramusers in SMAN 93 Jakarta. The study involved 152 teenagers as participants. The data was collected usinga simple randomsamplingtechnique. Bivariate correlationanalysis showed a negative relationship between social comparison and psychological well-being with ð‘Ÿ = -0.542 and ð‘ = 0.000 < ð‘ = 0.05. There was also a negative relationship between body dissatisfaction and psychological well-being with ð‘Ÿ = -0.472 and ð‘ = 0.000 < ð‘ = 0.05. Multivariate correlation regression analysis revealed a significant relationship between social comparison, body dissatisfaction, and psychological well-being with ð‘…=0.546 and ð‘ = 0.000 < ð‘ = 0.05, with the coefficient of determination (R Square) being 0.298. This indicates that social comparison and body dissatisfaction contribute to 29.8% of psychological well-being, while 70.2% is attributed to other unexamined factors. Such as self esteem, self concept and social support.